Degree of Manifestation of Emotional Style Dimensions in Primary School Teachers - Fetti (Mora); Ion Albulescu (Babes-Bolyai University, 2024)
Adopting an Emotional Style by the classroom teacher implies the emotional maturity of the personality expressed in emotional skills: awareness of emotional states, emotional balance and discipline, expression of feelings reflected in a style of conduct. The difference between other teaching styles and the emotional one comes from the focus on individual roles. The education of students is directly dependent on teachers, mentors, tutors or coaches, who have a strong influence in their educational journey and a well-defined role in their lives.